Unpacking the complex interactions among customers in online fan pages - Farmaki, Anna; Olya, Hossein; Taheri, Babak (My University, 2021)
Using the theories of complexity and the spiral of silence, this paper aims to understand how combinations of perceived news, brand gender, and participation explain conditions leading to brand love and customers’ attitudinal loyalty within online contexts. Drawing from a two-stage, mixed-method approach, results indicate that passive participation and brand masculinity are necessary to increase love and attitudinal loyalty to a brand, while perceived news informativeness and entertainment, brand femininity, and active participation are sufficient but not necessary. The study offers theoretical and practical insights that may guide further research and strengthen marketing attempts to improve customer engagement with online fan pages.
Keywords: Online fan pages; Perceived news; Brand gender; Participation; Brand love; Attitudinal loyalty